Homo Seksual Potret Perilaku Seksual Menyimpang Dalam Perspektif Kriminologi, Islam dan Budaya Melayu - Neri Widya Ramailis (SISI LAIN REALITA, 2017)
Homosexual is a term used to describe the general tendency of sex with other people of the same genes. Measures of deviant behavior are not in the right or completely wrong size in the general sense, which occur based on the size or absence of norms and values ​​of their sociality. If viewed from the aspect of criminology, deviant behavior becomes something that deviates from the limits determined by the norms and society. Lessons about Malay culture are inseparable from Islamic teachings which are the foundation of customs. Therefore the philosophy of Malay people says "Adat Bersendi Syarak, Syarak Bersendikan Kitabullah". From this sentence, it can be interpreted that religion and customs that grow and develop in Malay culture are very different. Where values, religious norms and rules that apply in the community are highly upheld in the life and culture of Malay people. Al-Qur'an as a book that is a source of guidance is the main basis of the handle of human life in carrying out daily activities, whether it is about how someone communicates with others and behaves in accordance with reasonable customs and culture. In this context homosexual behavior is seen as one manifestation of human behavior with deviant sexual orientation present in the community through a process of cultural development that is not good and immoral.